2014
DOI: 10.1002/ijc.28905
|View full text |Cite
|
Sign up to set email alerts
|

Parental cancer: Health‐related quality of life and current psychosocial support needs of cancer survivors and their children

Abstract: The presence of cancer and additional parental responsibilities can increase strain for individual patients as well as for their children. The construct of health‐related quality of life (HRQL) is appropriate to measure a combination of physical, mental and social consequences as a result of disease. However, previous research has merely focused on symptom checklists. This study addresses the following questions: (i) does HRQL in children and their parents with cancer differ compared to the general population?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 34 publications
7
47
2
6
Order By: Relevance
“…Primary school children experienced a higher totality of internalizing and externalizing problems [25,28], and ill parents perceived latency-aged primary school sons as having more emotional and behavioral problems than adolescent sons [24]. For older children, internalizing problems were more prevalent [28], as was a reduced quality of life [59], although one study suggested that older children experienced less problems in response to parental cancer, due to their advanced capabilities and independence [28]. Regardless, it appeared that older children had more responsibilities, including financial [58].…”
Section: Impact Of Cancermentioning
confidence: 96%
See 4 more Smart Citations
“…Primary school children experienced a higher totality of internalizing and externalizing problems [25,28], and ill parents perceived latency-aged primary school sons as having more emotional and behavioral problems than adolescent sons [24]. For older children, internalizing problems were more prevalent [28], as was a reduced quality of life [59], although one study suggested that older children experienced less problems in response to parental cancer, due to their advanced capabilities and independence [28]. Regardless, it appeared that older children had more responsibilities, including financial [58].…”
Section: Impact Of Cancermentioning
confidence: 96%
“…Parent's mental health influenced children's internalizing problems [28,34,41] and quality of life [59,60], and children were more likely to struggle to adjust to their parent's diagnosis if the parent struggled to adjust [18]. Treatment complications increased the number of problems experienced by offspring [28], while treatment intensity impacted adolescent daughters and relapse impacted sons [24].…”
Section: Parenting Factors Mediating Impactmentioning
confidence: 96%
See 3 more Smart Citations